Observation of B+c → J/ψD+s and B+c → J/ψD*+s decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
The decays B+c→J/ψD+s and B+c→J/ψD*+s are observed for the first time using a dataset, corresponding to an integrated luminosity of 3 fb−1, collected by the LHCb experiment in proton-proton collisions at center-of-mass energies of √s=7 and 8 TeV. The statistical significance for both signals is in excess of 9 standard deviations. The following ratios of branching fractions are measured to be B(B+c→J/ψD+s)B(B+c→J/ψπ+)=2.90±0.57±0.24, B(B+c→J/ψD*+s)B(B+c→J/ψD+s)=2.37±0.56±0.10, where the first uncertainties are statistical and the second systematic. The mass of the B+c meson is measured to be mB+c=6276.28±1.44(stat)±0.36(syst) MeV/c2, using the B+c→J/ψD+s decay mode.
Im Titel sind "+" hochgestellt und "c" und "s" jeweils tiefgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 589
publisher error corrected 26 December 2013
Gesehen am 20.04.2021